miFRame: analysis and visualization of miRNA sequencing data in neurological disorders - Backes, Christina; Haas, Jan; Leidinger, Petra; Frese, Karen S.; Grossmann, Thomas; Ruprecht, Klemens; Meder, Benjamin; Meese, Eckart; Keller, Andreas (Journal of translational medicine, 2015)
While in the past decades nucleic acid analysis has been predominantly carried out using quantitative low- and high-throughput approaches such as qRT-PCR and microarray technology, next-generation sequencing (NGS) with its single base resolution is now frequently applied in DNA and RNA testing. Especially for small non-coding RNAs such as microRNAs there is a need for analysis and visualization tools that facilitate interpretation of the results also for clinicians.
Gesehen am 29.07.2020